Графоаналітичний методологічний підхід до вартісної оцінки родовищ корисних копалин - Матюха, В.В. (Економіка природокористування і сталий розвиток, 2019)
Уперше в економічній теорії запропоновано графоаналітичний метод вартісної оцінки родовищ корисних копалин. Розкрито особливості цього методологічного підходу, який ґрунтується на дисконтуванні грошових потоків з одночасним урахуванням схеми життєвого циклу родовищ корисних копалин і витрат у післяексплуатаційний період. Зазначено, що такий підхід дасть змогу отримати більш точну вартісну оцінку родовища або ділянки надр. The importance of cost estimation of mineral resources in modern economic theory is noted in the article. It is noted that all currently existing methodical and methodological approaches to the valuation of minerals by their economic nature are in fact an analysis of the economic feasibility of realization of investment projects for the development of deposits, which actually answers the question: is the investment project for the development of the field economically viable. Based on the analysis of literary sources, it is established that at the present stage of development of the world economy, the interest in the economic evaluation of the efficiency of development of mineral resources is not waning. However, methodological approaches are different and there is still no unity in them. Experts point out that the current methods require improvement due to the low accuracy of calculations, since the size of the cost estimate depends on the amount of rental payments for the use of mineral resources in mining and the starting price of the sale of a special permit for the development of deposits at auction. For the first time in the economic theory economics, a graphoanalytic method for the cost estimation of mineral deposits has been proposed. The features of this methodological approach based on integral calculus, including the integration of continuous functions, as well as the method of discounting cash flows with simultaneous consideration of the life cycle scheme of deposits, namely mining and geological conditions of mining are opened. The step-by-step sequence of realization of the proposed method is resulted. It is stated that this approach will allow to obtain a more exact cost estimate of a deposit or subsoil by taking into account the following factors: the life of the deposit, the market conditions of the mineral resources, capital and current expenses connected with extraction of minerals and costs of the subsoil user in the post-mining a period of time related to the closure of mines and quarries and the reclamation of disturbed lands formed during the extraction of minerals.